The Effect of Sleep Quantity and Quality on Adults\' Blood Pressure: Yazd, 2014-2015 - Hossein Fallahzadeh; Mohammad Hassan Lotfi; Jabbar Shafiei (Shahid Sadoughi University of Medical Sciences, 2017)
Introduction: Sleep is an essential part of life and is of utmost importance in preserving human health and performance. The quantity and quality of sleep can affect blood pressure. The objective of this paper was to determine the relationship of sleep quantity and quality with high blood pressure. Methods: This profile study utilized the data of Health Study Program in Yazd. The population contained 6964 adults in the age range of 20 to 70 years, selected using cluster sampling method. The data were analyzed using chi-squared (X2) and Logistic Regression tests via SPSS (ver. 18) software. Results: Generally, 50.3% of the participants were female, 28.6% of them had high blood pressure; 31.3% of men and 25.9% of women had high blood pressure. The lowest rate of blood pressure happened within participants with 20-29 years of age, i.e., 9.9%, while the highest rate was related to individuals of 60-69 years old, i.e., 49.6%. X2 test yielded significant results for sleep duration (p<0.001) and nightmare frequency (p=0.016). The adjusted chance of sleep duration, gender, age groups, educational levels, and body mass index (BMI) had significant effects on blood pressure (p<0.001). Half of the participants showed sleep dysfunctions in terms of quantity and quality, and one-third were likely to come down with high blood pressure. Conclusion: It can be concluded that the sleep quantity and quality of the studied people were not at a desirable level; it needs high attention. It can be maintained that the findings of the current study indicated the importance of paying attention to the quality and quantity of sleep in preventing the incidence of high blood pressure.